Stability of light steel walls in compression with plasterboards on one or both sides. Issue 6 (1st March 2019) - Lawson, R. Mark; Way, Andrew G. J.; Heywood, Martin; Lim, James B. P.; Johnston, Ross; Roy, Krishanu
Abstract : In light steel framing, the compression resistance of the walls may be improved by the stabilising effect of plasterboard attached to one or both sides of the wall. This paper presents the results of 28 load tests on 2·4 m high walls using 75, 100 and 150 mm deep C-sections in 1·2 to 1·6 mm thick steel with various types of board. The results were compared to the methodology in the standards BS EN 1993-1-3 and BS 5950-5, taking account of restraint to minor axis buckling. The test results showed that the lateral restraint provided by 12 or 15 mm thick fire-resistant or moisture-resistant plasterboard fixed to one flange is equivalent to an effective length reduction factor of 0·7 in the minor axis direction for a 100 mm × 1·6 mm C-section in a 2·4 m high wall. A theory is developed based on distortional buckling of the C-sections, which allows the test results to be extended to other wall heights and section sizes. The failure loads were predicted by finite-element modelling by considering initial imperfections in the C-sections and the torsional restraint due to the boards.